The situation with vaccination in Shkodra region after the first year of implementation of human papillomavirus vaccine - Zamira Shabani; Edona Haxhija; Emiljano Pjetri; Irena Shala; Nevila Bushati; Amela Malevija (Medičnì Perspektivi, 2025)
Human papillomavirus (HPV) is a common sexually transmitted infection with potentially serious health consequences, including anogenital and oropharyngeal cancers and genital warts. In 2022, Albania implemented an HPV vaccination program for girls aged 13-20 years, offering a single dose of the bivalent or quadrivalent vaccine. This study aims to evaluate the status of HPV vaccination in the Shkodra region after its first year of implementation and explore reasons for non-vaccination. This retrospective study collected data from official vaccination registers at health centers in the Shkodra region for the period 2022-2023. Additionally, face-to-face interviews were conducted with nurses responsible for administering vaccinations (vaccinators) and with parents present at the centers. Quantitative data were obtained and validated by the Chief Vaccination Office in the Epidemiology Sector at the Local Health Care Unit in Shkodra. A simple descriptive and comparative method was employed. Data for this study were gathered from two main sources: official vaccination records and interviews conducted with nurses and parents. Quantitative data were processed and analyzed using Microsoft Office Excel 2010. The vaccination coverage plan aimed to vaccinate 812 girls, with 67% (n=546) from urban areas and 33% (n=266) from rural areas. Overall, vaccination coverage was 51% (n=412 girls). Coverage was higher in rural areas (72.6%, n=193 girls) than in urban areas (40%, n=219 girls). This study highlights the challenges and successes of the HPV vaccination program in the Shkodra region during its first year of implementation. Vaccination coverage was higher in rural areas (72.6%) compared to urban areas (40%). Key barriers to vaccine uptake included parental refusal, lack of information, and fear of side effects.